(untitled) (قضايا سياسية, 2024)
The countries in the South and North Caucasus region have witnessed crises and wars that have caused political instability at the regional and international levels since the dissolution of the Soviet Union in December 1991. Crises and wars escalated in those countries and greatly affected regional and global security and stability, the most important of which was the Russian war In Chechnya in 1996, the subsequent confrontations and the emergence of extremist Islamic organizations in that era caused a state of political instability and regional security The republics in the Caucasus region were divided into two parts, the first part, which included the republics of the North Caucasus, located south of the Russian Federation, which remained within the sovereignty of the Federal Republic of Russia, and witnessed conflicts and wars that attempted independence or secession from the Russian Federation, but to no avail, and the second part includes the republics located in The South Caucasus, which gained independence from the Russian Federation, is the three republics that formed the countries of the South Caucasus: Georgia, Armenia, and Azerbaijan . Despite the independence of the three South Caucasus countries from the Russian Federation, these countries did not witness political and security stability due to crises, internal conflicts, and regional and international interventions in those three republics after the events of September 11, 2001. The crises between Armenia and Azerbaijan escalated repeatedly until they reached To the military clash between the two countries, and the impact of the escalation of the conflict on the stability and national security of neighboring regional countries, the most important of which are the Russian Federation, Turkey and Iran. The region also witnessed a military clash in the first decade of the twenty-first century, which was represented by the outbreak of the Russian war against Georgia in 2008, While Turkish relations with Armenia witnessed constant tensions, as well as border conflicts between those countries, especially Armenia and Azerbaijan, the most recent of which was the military escalation on the border between them in 2021, all of these crises had a large and important impact on the internal political stability of those countries and the regional security of neighboring countries. Regionally, such as the Russian Federation, Turkey, and Iran, as well as the impact of these crises at the international level.